Portal Area Perumahan dengan NODEMCU, Aplikasi WEB dan Android Berbasis IoT - Mochamad Fajar Wicaksono; Myrna Dwi Rahmatya (Universitas Multimedia Nusantara, 2021)
The access time of using the portal in certain blocks in a residential area can be a problem for some residents. Another problem that arises is if the officer holding the portal key is not in place. The purpose of this study is to create a system to regulate access rights to a particular block within a residential area so that the opening and closing of the portal can be done at any time by residents in the intended area. There are several blocks of this system, namely the NodeMCU controller block, ESP32CAM, Android applications, and web applications that are built using the PHP and MySQL programming languages. NodeMCU is used as the main controller to manage servo motors, send and receive data to and from the server, receive input related to open and close portals from the android application. The web application is used to register users, view the portal usage log, and verify the login process of the application. This system has been running well based on the results of tests that have been carried out, where the registration process, login, opening and closing portals, log usage is in accordance with the objectives to be achieved. Index Terms—Portal; NodeMCU; ESP32CAM; Android; Web Application